Bullying in pesantren and its mitigation - Pratiwi, Dewi; Pandang, Abdullah; Aryani, Farida (Program Studi bimbingan Konseling PPs UNM Makassar, 2024)
This study aims to investigate the forms, impacts, and factors of bullying, along with the efforts to mitigate bullying impacts on the victims. This case study adopted a qualitative descriptive approach. Data were collected through observations, interviews, and documentation. The Miles and Huberman analysis model was used interactively and consistently to analyze the data, ensuring a comprehensive understanding of the case context being studied. The research subject was a single individual who experienced bullying at the Multazam Bontonompo Pesantren. The results showed that: 1) the victim experienced physical, verbal, and social forms of bullying; 2) the bullying was attributed to both internal and external factors; and 3) an assertive training technique was implemented as an effort to mitigate bullying impacts on the victim, who gradually showed improvement